Staging a conference to frame war as a public health problem - Rebecca Bartlein; Evan Kanter; Daren Wade; Amy Hagopian (Social Medicine Publication Group, 2013)
"War & Global Health: Transforming Our Professions, Changing our World," a conference organized at the University of Washington in the spring of 2010 by the Department of Global Health in the School of Public Health and Physicians for Social Responsibility, aimed to promote a public health approach to war and frame the prevention of war as a legitimate and imperative academic endeavor. The conference planners drew on substantial, yet under-acknowledged, work on the health consequences of war in both research and practice. They considered historical lessons on how a human behavior with negative consequences-generated by political and economic forces-can be framed as a health issue by health professionals. Key elements in the planning and execution of the conference were a strategic partnership between an academic department and an activist organization and the harnessing of considerable student energies. Conference organizers built on a policy statement adopted by the American Public Health Association in 2009 outlining the responsibility of public health professionals to prevent war. The authors document the important elements and the convergence of forces that resulted in a successful conference, examine the lessons learned, and offer a Web-based resource for those interested in staging a similar event.